2019
DOI: 10.1113/jp278292
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic recruitment of spinal reflex pathways from large‐diameter primary afferents in non‐transgenic rats transduced with AAV9/Channelrhodopsin 2

Abstract: Key points We demonstrated optical activation of primary somatosensory afferents with high selectivity to fast‐conducting fibres by means of adeno‐associated virus 9 (AAV9)‐mediated gene transduction in dorsal root ganglion (DRG) neurons. AVV9 expressing green fluorescent protein showed high selectivity and transduction efficiency for fast‐conducting, large‐sized DRG neurons. Compared with conventional electrical stimulation, optically elicited volleys in primary afferents had higher sensitivity with stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Various AAV vectors, including AAV2, demonstrate neuronal tropism ( Mason et al, 2010 ; Fischer et al, 2011 ). Several AAV serotypes exhibit differential tropism for specific subpopulations of DRG neurons: AAV6 preferentially transduces small-sized neurons; AAV5, 8, and 9, large neurons ( Jacques et al, 2012 ; Yu et al, 2013 ; Wu et al, 2016 ; Kubota et al, 2019 ). We found that AAV2 preferentially transduces NF+ neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Various AAV vectors, including AAV2, demonstrate neuronal tropism ( Mason et al, 2010 ; Fischer et al, 2011 ). Several AAV serotypes exhibit differential tropism for specific subpopulations of DRG neurons: AAV6 preferentially transduces small-sized neurons; AAV5, 8, and 9, large neurons ( Jacques et al, 2012 ; Yu et al, 2013 ; Wu et al, 2016 ; Kubota et al, 2019 ). We found that AAV2 preferentially transduces NF+ neurons.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 However, other serotypes of AAV vectors exhibit different target specificity to DRG neurons. For example, AAV8 and AAV9 vectors have been reported to be effective in delivering genes into large-diameter DRG neurons 22 , 23 that signal deep muscle and tactile sensations, but not nociception. Furthermore, by taking advantage of the target specificity of AAV vectors, the use of optogenetics to selectively modulate nociceptive, 20 , 21 , 24 , 25 , 26 as well as non-nociceptive, 23 , 26 DRG neuron activity has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AAV8 and AAV9 vectors have been reported to be effective in delivering genes into large-diameter DRG neurons 22 , 23 that signal deep muscle and tactile sensations, but not nociception. Furthermore, by taking advantage of the target specificity of AAV vectors, the use of optogenetics to selectively modulate nociceptive, 20 , 21 , 24 , 25 , 26 as well as non-nociceptive, 23 , 26 DRG neuron activity has also been reported. Similarly, sustained relief of chronic pain has been achieved in a rodent model, by target-selective delivery of calcium ion (Ca 2+ ) channel-related peptides, together with the AAV6 vector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with dorsal roots removed, optogenetic excitation of central terminals of primary afferent neurons is sufficient to produce postsynaptic responses in spinal cord neurons (Wang and Zylka, 2009;Foster et al, 2015). For an investigation of primary afferent-evoked responses within the spinal cord, optogenetic stimulation provides the benefit of selectively stimulating a genetically distinct subset of primary afferents, as compared to electrical stimulation (Tashima et al, 2018;Kubota et al, 2019). This provides unparalleled specificity to define circuitry within the spinal cord.…”
Section: In Vitro Spinal Cord Optogeneticsmentioning
confidence: 99%